Structural Health Assessment of Kretek II Bridge using Enhanced Frequency Domain Decomposition - Astalis Ulul Absor, Didib; Aminullah, Akhmad; Supriyadi, Bambang (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2024)
The development of infrastructure is growing rapidly in Indonesia. Kretek II bridge is one of the infrastructures built in the country. Dynamics aspects are one of the very important aspects used to validate structural analysis model or being linked to Structural Health Monitoring (SHM) of the bridge. Dynamics properties such as natural frequency, damping ratio, and mode shape also referred as modal parameters. The objective of this research is to determine the modal parameters of Kretek II bridge using Enhanced Frequency Domain Decomposition (EFDD) which is commonly used to extract modal parameters from the acceleration data recorded. Compared to the conventional method, EFDD is very practical and robust in structural health assessment because of its user-friendly uses in the ARTeMIS Modal software. To make sure that the results from EFDD are accurate, numerical modeling is necessary to validate it. This research was conducted using dynamics load test results as data for the modal extraction with EFDD method assisted by ARTeMIS Modal software. Dynamics load test was performed by placing 8 accelerometers in the span and exciting it with impact load from dropped truck on ramp. Modal parameters from the EFDD results are then compared to the numerical modeling results. The first two modes of the EFDD and numerical modeling results consecutively are 3.09 Hz, 3.745 Hz and 3.06 Hz, 3.49 Hz. The EFDD and numerical modeling results are both in agreement with both results having similar mode shape on their first two mode and low error percentage with only 0.89% and 7.17% respectively.